2003
DOI: 10.1182/blood-2002-07-2175
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced thrombocytopenia: localization of the binding site of GPIX-specific quinine-dependent antibodies

Abstract: Immune thrombocytopenia is a common complication of therapy with a large number of drugs. The most widely studied drug-induced immune thrombocytopenia (DIT) is caused by quinine. In most cases of DIT, antibodies bind to the platelet membrane glycoprotein (GP) Ib-IX complex in a drug-dependent fashion and bring about increased platelet clearance by the reticuloendothelial system resulting in thrombocytopenia. Here, we report the characterization of the quinine-dependent antibody activity of sera from 13 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…4 Although the introduction of RIC regimens has resulted in a decrease in the high incidence of TRM associated with myeloablative conditioning, an intense debate is currently ongoing regarding the question of whether patients should be subjected to the substantial morbidity, especially graft-versushost disease (GVHD), and the risk of mortality associated with RIC allo-SCT as part of first-line therapy compared with the relatively safe procedure of auto-SCT. [5][6][7][8][9][10][11] Lokhorst et al performed a donor versus no-donor analysis of patients included in the phase 3 HOVON-50 MM trial. 1 After a single auto-SCT, eligible patients were randomized according to the availability of an HLA-identical sibling to receive either maintenance therapy consisting of thalidomide or ␣-interferon or RIC allo-SCT after low-dose 2 Gy total body irradiation.…”
Section: Philippe Moreau University Hospital Nantesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Although the introduction of RIC regimens has resulted in a decrease in the high incidence of TRM associated with myeloablative conditioning, an intense debate is currently ongoing regarding the question of whether patients should be subjected to the substantial morbidity, especially graft-versushost disease (GVHD), and the risk of mortality associated with RIC allo-SCT as part of first-line therapy compared with the relatively safe procedure of auto-SCT. [5][6][7][8][9][10][11] Lokhorst et al performed a donor versus no-donor analysis of patients included in the phase 3 HOVON-50 MM trial. 1 After a single auto-SCT, eligible patients were randomized according to the availability of an HLA-identical sibling to receive either maintenance therapy consisting of thalidomide or ␣-interferon or RIC allo-SCT after low-dose 2 Gy total body irradiation.…”
Section: Philippe Moreau University Hospital Nantesmentioning
confidence: 99%
“…In contrast, different mechanisms have been described for other immune drug-induced thrombocytopenias. 3,7,8 Here, Bougie and colleagues directly investigated this issue and found that patient antibodies did not recognize LIB determinants as previously expected but instead recognized conformational changes in ␣ IIb ␤ 3 induced by the drug. 1 In the majority of patients with eptifibatide-and tirofiban-induced thrombocytopenia (30 of 43 patients), antibody binding was drug specific and only occurred when the For personal use only.…”
mentioning
confidence: 99%
“…This might be particularly true for flow cytometry, because of its wide availability in clinical laboratories and its potential suitability to identify several different drugs. The only comparison between flow cytometry and MAIPA for detecting quininedependent antibodies in 13 patients showed a lower sensitivity of flow cytometry [11], and thus MAIPA remains the gold standard test.…”
Section: Discussionmentioning
confidence: 99%
“…Drug binding to platelet surface can form a new epitope or cause the exposure of a neo-epitope. Glycoprotein Ib-IX and GP IIb/IIIa are most frequently involved in drug binding, which leads to the formation of new epitopes that appear to be very specific for each different drug [6][7][8][9][10][11][12][13][14]. The development of drug-dependent antiplatelet antibodies may thus cause accelerated platelet clearance in vivo and induce severe thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation